A call for change: addressing the implementation strategy using pre exposure Prophylaxis for combating the escalating HIV crisis in Zanzibar’s key populations - Mshenga, Mansour Maulid; Tang, Weiming (AIDS research and therapy, 2024)
The Integrated Bio-Behavioural Surveillance Survey of 2022–2023 among key populations report from Zanzibar has been released. The prevalence of HIV is estimated to be 21.1%, 11.4%, and 9.3% among Female Sex Workers, Men who have Sex with Men, and People Who Injected Drugs, respectively. This has prompted a closer examination of the factors contributing to this trend, with a particular focus on the low coverage of Pre-Exposure Prophylaxis in these key populations. The current prevalence reported in December 2023 signals a critical turning point that necessitates a reevaluation of the barriers and facilitators of Pre Exposure Prophylaxis intervention to combat the epidemic. It is imperative to acknowledge the severity of the situation and take decisive action to prevent further spread of the virus in the Isles.